2016
DOI: 10.1002/cm.21290
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of the tubulin code: From the tubulin molecule to neuronal function and disease

Abstract: Across different cell types and tissues, microtubules are assembled from highly conserved dimers of a-and b-tubulin. Despite their highly similar structures, microtubules have functional heterogeneity, generated either by the expression of different tubulin genes, encoding distinct isotypes, or by posttranslational modifications of tubulin. This genetically encoded and posttranslational generated heterogeneity of tubulinthe "tubulin code"-has the potential to modulate microtubule structure, dynamics, and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
112
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(113 citation statements)
references
References 126 publications
(165 reference statements)
1
112
0
Order By: Relevance
“…The expression or function of other microtubule regulators, such as survivin Rosa et al, 2006), ATIP3 (Molina et al, 2013;Velot et al, 2015) and the +TIPs EB1 (Liu et al, 2009;Stypula-Cyrus et al, 2014) and APC (Etienne-Manneville, 2009), was found to be altered in certain cancers, but the exact role of these proteins in 3D cell migration is still unclear. Mutations in genes encoding tubulin isoforms and different microtubule regulators including +TIPs have also been associated with neurodevelopmental diseases, including disorders of neuronal migration (Breuss and Keays, 2014;Chakraborti et al, 2016;van de Willige et al, 2016), and it will be interesting to investigate which of their functions reflect general mechanisms of 3D cell motility and which are neuron specific.…”
Section: Microtubule Alteration and Diseases Related To Cell Migrationmentioning
confidence: 99%
“…The expression or function of other microtubule regulators, such as survivin Rosa et al, 2006), ATIP3 (Molina et al, 2013;Velot et al, 2015) and the +TIPs EB1 (Liu et al, 2009;Stypula-Cyrus et al, 2014) and APC (Etienne-Manneville, 2009), was found to be altered in certain cancers, but the exact role of these proteins in 3D cell migration is still unclear. Mutations in genes encoding tubulin isoforms and different microtubule regulators including +TIPs have also been associated with neurodevelopmental diseases, including disorders of neuronal migration (Breuss and Keays, 2014;Chakraborti et al, 2016;van de Willige et al, 2016), and it will be interesting to investigate which of their functions reflect general mechanisms of 3D cell motility and which are neuron specific.…”
Section: Microtubule Alteration and Diseases Related To Cell Migrationmentioning
confidence: 99%
“…Consistent with this hypothesis, distinct roles of tubulin isotypes have been implicated. In humans, mutations of different tubulin isotypes cause distinct neurological disorders (for reviews, see Chakraborti et al, 2016;Romaniello et al, 2015). In Drosophila, a testis-specific isotype cannot be replaced by a somatic isotype (Fackenthal et al, 1993;Hoyle and Raff, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…One possibility is that these mutations introduce very subtle changes into the tubulin structure, which only marginally affect MT functions. These defects would only become apparent in cellular processes (such as neuronal migration) that essentially depend on fine-tuned MT dynamics (discussed in detail in Chakraborti et al, 2016). Even more intriguingly, mutations of different amino acid residues in the same tubulin isotype can have distinct pathological outcomes.…”
Section: Box 1 Tubulin Mutationsmentioning
confidence: 99%
“…The phenotypes generated by these mutations could be explained in different ways. One possibility is that single amino-acid replacements slightly alter the properties of tubulin, which can be tolerated in most MT functions but result in aberrations in some particularly challenging functions, such as longrange neuronal migration (discussed in Chakraborti et al, 2016). Indeed, single mutations in different isotypes can affect GTP hydrolysis and catastrophe rate of MTs (Geyer et al, 2015), as well as MT dynamic instability .…”
Section: Molecular Mechanisms Of Isotypesmentioning
confidence: 99%
See 1 more Smart Citation